Hamstring injury prevention in soccer: Before or after training? - Lovell, R.; Knox, M.; Weston, M.; Siegler, J. C.; Brennan, S.; Marshall, P. W. M. (Scandinavian Journal of Medicine & Science in Sports, 2018)
We examined the effects of a 12-week program of Nordic hamstring exercises (NHE), administered before or after football training, upon eccentric hamstring strength, muscle activity, and architectural adaptations. Amateur soccer players were randomized into 3 groups. The control group (CON; n=11) undertook core stability exercises, whereas a periodized NHE program was delivered either before (NHEBEF; n=10) or after (NHEAFT; n=14) bi-weekly training sessions. Outcome measures included peak torque and concomitant normalized peak surface electromyography signals (sEMG) of the biceps femoris (BF) and medial hamstring (MH) muscles during knee flexor maximal eccentric contractions, performed at 30°·s-1. Ultrasonography was used to determine BF muscle thickness, muscle fiber pennation angle, and fascicle length. Performing the NHE derived likely moderate peak torque increases in both NHEBEF (+11.9%; 90% confidence interval: 3.6% to 20.9%) and NHEAFT (+11.6%; 2.6% to 21.5%) versus CON. Maximum sEMG increases were moderately greater in the BF of both NHE training groups versus CON. There were likely moderate increases in BF muscle thickness (+0.17 cm; 0.05 cm to 0.29 cm) and likely small pennation angle increases (+1.03°; -0.08° to 2.14°) in NHEAFT versus CON and NHEBEF. BF fascicle length increases were likely greater in NHEBEF (+1.58 cm; 0.48 cm to 2.68 cm; small effect) versus CON and NHEAFT. A 12-week eccentric hamstring-strengthening program increased strength and sEMG to a similar magnitude irrespective of its scheduling relative to the football training session. However, architectural adaptations to support the strength gains differed according to the timing of the injury prevention program.